Aplikasi Sistem Pakar Untuk Menentukan Pemberian Kredit Modal Kerja = An application of Expert System to Determine Working Capital Credit - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT An Application of Expert System has been built to analysis credit approval given by bank and determine whether the proposed credit accepted or deny. Architecture of expert system was deployed by knowledge base, inference engine, user interface, and explanation facility. The knowledge base includes knowledge about all aspects of conditions owned by debtor candidate and the rules to do analysis credit approval. Backward chaining method has been used in inference engine. To analysis credit approval via friendly user interface to communicate between user and system. The explanation facility give an information for user. The final result of this research is the expert system which capable to assist working capital credit. The system output is interface with interactive dialog, a credit analyst using this interface to answers system questions regarding to the credit approval analysis and also fill in the required certainty factor. The experimental result shows that the system is capable of doing analysis to the proposed credit and determine whether it is accept or deny.